Evaluation of Microplastic Content in Human Circulatory System and Its Potential Impacts on Systemic Health - Kun Mardiwati Rahayu; Mila Sari; Pratiwi Ratih Halimatus Sya'diah (Science Journal Get Press, 2026)
Given the escalating global production of plastics and the absence of regulatory frameworks addressing internal human exposure, microplastic contamination has emerged as an urgent environmental and public health policy concern.Using micro Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy, MPs were detected in 76.0% of samples collected from 50 healthy adults, with an average concentration of 3.15 ± 1.25 particles/mL and a mean particle size of 5.8 ± 2.1 μm. Polyethylene terephthalate (PET) and polypropylene (PP) were the dominant polymer types, while fragments and fibers represented the most common morphologies. Correlation analyses revealed significant positive associations between total MP concentration and inflammatory biomarkers C-reactive protein (r = +0.415, p = 0.003) and interleukin-6 (r = +0.288, p = 0.043) as well as oxidative stress marker malondialdehyde (r = +0.350, p = 0.013), suggesting that MPs may contribute to subclinical systemic inflammation and oxidative imbalance. These findings provide empirical evidence supporting the systemic circulation of MPs and their potential role as low-grade biological stressors that could influence vascular homeostasis. Further longitudinal and mechanistic studies are warranted to elucidate causal pathways, characterize nanoplastic fractions, and establish standardized analytical protocols. This research underscores the growing necessity to treat microplastic exposure as a critical environmental and public health issue.